Answer:
Step-by-step explanation:
Answer:
(-5,17) is a solution to the equation
Step-by-step explanation:
The equation is y = -2x+7
Substitute the values of x=-5 and y =17 into the equation and see if it is true
17 = -2(-5) +7
17 = 10+7
17=17
This is true so (-5,17) is a solution to the equation
The answer should be prime. You can’t factor that polynomial
For this case we have the following expression:
3sqrt (8) / 4sqrt (6)
Rewriting we have:
3sqrt (2 * 4) / 4sqrt (6)
3 * 2sqrt (2) / 4sqrt (6)
6sqrt (2) / 4sqrt (6)
3sqrt (2) / 2sqrt (6)
3sqrt (2) / (2sqrt (2) sqrt (3))
3 / (2sqrt (3))
3sqrt (3) / (3 * 2)
sqrt (3) / (2)
Answer:
the following quotient is:
D.sqrt 3/2
The product of 3 and x is 3x and the given above can be expressed as,
3x - 9 = (1/2)(x + 12)
I assume that the problem asks for the value of x. Solving for x in the equation above gives x = 6.
Thus, the answer is 6.